Kajian Perilaku Kera Ekor Panjang (Macaca fascicularis) dan Lutung (Trachypithecus auratus) di Coban Rondo, Kabupaten Malang - Anwari Adi Nugroho; Sugiyarto S (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Coban Rondo is a waterfall located in Pujon, Malang, East Java. Apes and monkeys are animals that are most prevalent along the Coban Rondo. Two species of monkeys that inhabit the area Coban Rondo is a long-tailed Macaques (Macaca fascicularis) and monkey (Presbytis cristata). Long-tailed macaque (Macaca fascicularis) monkeys are native to Southeast Asia but is now scattered in various places in Asia. The research focuses on the study of the behavior of long-tailed macaques Length (Macaca fascicularis) and monkey (Trachypithecus auratus) in Coban Rondo, Malang. The method used is observation and interviews with local people. The results showed that the Long-tailed Macaques (Macaca fascicularis) and monkey (Trachypithecus auratus) in Coban Rondo, Malang has a different behavior covering obtain food, residing, and reproduce. Two types of primates that have different behaviors in the same location, but able to coexist.Keywords: behavior, Coban rondo, Macaca fascicularis, Trachypithecus auratus